2017
DOI: 10.1093/aje/kww120
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effect of Genetic Variants Associated With Body Mass Index on Multiple Sclerosis Susceptibility

Abstract: Multiple sclerosis (MS) is an autoimmune disease with both genetic and environmental risk factors. Recent studies indicate that childhood and adolescent obesity double the risk of MS, but this association may reflect unmeasured confounders rather than causal effects of obesity. We used separate-sample Mendelian randomization to estimate the causal effect of body mass index (BMI) on susceptibility to MS. Using data from non-Hispanic white members of the Kaiser Permanente Medical Care Plan of Northern California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 43 publications
(44 reference statements)
8
45
0
Order By: Relevance
“…The association with obesity and vitamin D levels may also have an underlying genetic basis. Obesity risk alleles identified by a genome‐wide association study demonstrated a causal association with paediatric multiple sclerosis after adjustment for age, sex, ancestry, the HLA‐DRB1*15:01 allele, and over 100 non‐HLA multiple sclerosis risk variants . The same study used three genetic variants known to affect serum concentrations of 25‐hydroxy‐vitamin D levels to compute a genetic risk score which estimated the effect of each risk variant.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 99%
See 1 more Smart Citation
“…The association with obesity and vitamin D levels may also have an underlying genetic basis. Obesity risk alleles identified by a genome‐wide association study demonstrated a causal association with paediatric multiple sclerosis after adjustment for age, sex, ancestry, the HLA‐DRB1*15:01 allele, and over 100 non‐HLA multiple sclerosis risk variants . The same study used three genetic variants known to affect serum concentrations of 25‐hydroxy‐vitamin D levels to compute a genetic risk score which estimated the effect of each risk variant.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 99%
“…Obesity risk alleles identified by a genome-wide association study 56 demonstrated a causal association with paediatric multiple sclerosis after adjustment for age, sex, ancestry, the HLA-DRB1*15:01 allele, and over 100 non-HLA multiple sclerosis risk variants. 57 The same study used three genetic variants known to affect serum concentrations of 25-hydroxy-vitamin D levels to compute a genetic risk score which estimated the effect of each risk variant. The genetic risk score associated with increasing serum concentrations of 25-hydroxy-vitamin D decreased the odds of paediatric-onset multiple sclerosis.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 99%
“…However, Th1-like T regs have also been described in models of chronic infection ( 8688 ) and patients with type one diabetes (T1D) ( 26 ). Furthermore, childhood obesity has been linked as a risk factor for the development of MS ( 89–92 ). Therefore, using MS as our model, we used single cell RNA-sequencing to profile 1,334 T regs from peripheral blood and 805 T regs from adipose tissue of eight healthy donors and eight MS patients, two of whom are untreated (> ~1.5yrs at the time of the procedure), and the rest had previously received disease modifying treatments (DMTs) (> 6 months prior to the procedure, but were currently off treatment) (Supplemental Figure 10, Supplemental Figure 12, and Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to determine a causal association between obesity and MS susceptibility have recently been conducted 41,42 . Mendelian randomization is a type of instrumental variable (IV) analysis that uses genetic variants strongly associated with an exposure, rather than a direct measure of the exposure, to estimate the effect of the exposure on an outcome.…”
Section: Evidence Of a Causal Associationmentioning
confidence: 99%
“…One study indicated that obesity is causally associated with MS onset using an IV composed of 97 genetic variants associated with BMI 42 . Authors confirmed the results in two populations, and also found evidence that five BMI-associated genes had a direct effect on MS susceptibility.…”
Section: Evidence Of a Causal Associationmentioning
confidence: 99%